Monitoring glutathione dynamics in DNA replication (S-phase) using a two-photon reversible ratiometric fluorescent probe. Issue 9 (7th February 2023) - Biswas, Shayeri; Sarkar, Sourav; Dhamija, Avinash; Murali, Vishnu Priya; Maiti, Kaustabh Kumar; Bhuniya, Sankarprasad
Abstract : A smart self-calibrated reversible fluorescent probe Nu-GSH has provided GSH dynamics in the nucleus. The temporal fluctuation of the nuclear GSH reciprocated the depletion of the S-phase in the cell cycle process. Abstract : The redox regulator glutathione (GSH) migrates to the nucleus to give a safeguard to DNA replication in the S-phase. The fluctuation of GSH dynamics in the cell cycle process may help to understand cancerogenesis or other abnormalities in DNA replication. For the first time, we attempted to track the time-dependent S-phase change using the newly developed ratiometric fluorescent probe Nu-GSH . This probe is highly chemoselective towards glutathione and shows an emission intensity shift from 515 nm to 455 nm. It has shown fluorescence reversibility from blue to green channels while scavenging reactive oxygen species H2 O2 . Both ratiometric fluorescence images and FACS analysis have provided quantitative information on the GSH levels in the nucleoli during DNA replication in the S-phase. Furthermore, GSH fluctuation reciprocated the decay of the S-phase on a time scale. Additionally, its two-photon ability guaranteed its capability to study GSH dynamics in live cells/tissues noninvasively. We envision that the probe Nu-GSH can be used to get high-throughput quantitative information on glutathione dynamics and give an opportunity to monitor its perturbation during the course of cell division.